Quintessence and the Higgs Portal in the Carroll Limit - Gamboa-Rios, J; Mendez-Ferrada, F (Elsevier B.V., 2024)
A cosmological model based on two scalar fields is proposed. The first of these, φ, has mass μ, while the second, χ, is massless. The pair are coupled through a “Higgs portal”. First, we show how the model reproduces the Friedmann equations if the square of the mass of the φ field is proportional to the cosmological constant and χ represents the quintessence field. Quantum corrections break the conformal symmetry, and the χ field acquires a mass equal to 3gΛ. The perturbative approach with g≪1 is consistent with the bounds for mχ; moreover, by using dimensional analysis, we estimate mχ≪H0≈10−33 eV, which is in accordance with what is expected in the quintessence scenario. The acceleration of the universe is proportional to χ2, we conclude that for very long times, the solution of the equation of motion approaches 〈χ〉∼mχ/λ and the universe continues to accelerate, with a constant acceleration. © 2024 The Author(s)